MARKETING OF LIBRARY AND INFORMATION SERVICES: BUILDING A NEW DISCIPLINE FOR LIBRARY AND INFORMATION SCIENCE EDUCATION IN ASIA - Gupta, Dinesh K. (Malaysian Journal of Library and Information Science, 2003)
The concept of marketing is widely applicable in library and information environment. Marketing concept itself is changing and has different meaning for different people. Now marketing is whole organization concept and organization wide philosophy, which requires years of continual work. It is a way of working and a way of serving the customers in which every activity is committed to customer satisfaction. Marketing of library services is the effective execution of all the activities involved in increasing satisfaction of users by providing maximum value to them. It is a total solution for library and information centers. There have been enormous developments in marketing of library and information services around the world. The present paper explores the discipline of marketing of library services as a new academic subject in library and information education focusing on the Indian experience